IMPROVEMENT OF PEDAGOGICAL ABILITIES ON THE BASIS OF AN INTEGRATIVE APPROACH - Xasanova Gulnoza (Web of Journals Publishing, 2024)
This article talks about the content of the integrative approach in improving the pedagogical skills of preschool teachers.
Keywords: Professional skill, psychological knowledge, strong will, pedagogical skill, skill, educator model, educational effectiveness, humane attitude.